Prospective study on the risk of transmission due to droplets and aerosols during an endoscopic procedure and the usefulness of extraoral suction devices. Issue 3 (11th October 2022) - Sunakawa, Hironori; Yoda, Yusuke; Takahashi, Mari; Arai, Keisuke; Kano, Yuki; Yamashita, Hiroki; Aoyama, Naoki; Mitsui, Tomohiro; Inaba, Atsushi; Takashima, Kenji; Nakajo, Keiichiro; Murano, Tatsuro; et al.
Abstract : Objectives: Endoscopy poses a high risk of severe acute respiratory syndrome coronavirus 2 infection for medical personnel due to the dispersal of aerosols from the patient. We investigated the location and size of droplets generated during esophagogastroduodenoscopy (EGD) and endoscopic submucosal dissection (ESD), the contamination of the surrounding area before and after the procedures, and the effectiveness of using an extraoral suction device (Free arm arteo; TOKYO GIKEN, Inc., Tokyo, Japan). Methods: Patients who consented to the study and underwent EGD or ESD between December 8, 2020, and April 15, 2021, at the National Cancer Center East Hospital were included. Adenosine triphosphate (ATP) hygiene monitoring tests and a particle counter were used for measurements. Results: Assessments were performed on 22 EGD and 15 ESD cases. ATP hygiene monitoring tests showed significant elevations at three sites near the patient, and two sites 1.5 m away, for EGD, and at four sites near the patient and 1.5 m away for ESD. In both ESD and EGD, extraoral suction devices reduced the extent of the contamination. Particles <5 μm in size were generated during endoscopic procedures and dispersed from both the forceps hole and the patient's mouth. The extraoral suction device did not reduce the number of particles generated. Conclusions: During endoscopic procedures, cleaning the surrounding environment is important in addition to standard precautions the endoscopist and caregivers take. The use of extraoral suction devices can also potentially reduce contamination of the surrounding environment.